FiberCreme Addition in Rice Increases the Dietary Fiber, Resistant Starch and Decreases Glycemic Index - Fibri, Dwi Larasatie Nur; Marsono, Yustinus (Department of Technology of Agricultural product (THP) Jambi University, 2024)
A study on the addition of FiberCreme in cooking of rice has been conducted. The aim was to evaluate the effect of adding FiberCreme when cooking rice on chemical composition, dietary fiber and resistant starch of cooked rice as well as the glycemic index of rice with FiberCreme added. FiberCreme is a non-dairy creamer composed of coconut oil as the source of fat and dietary fiber as source of carbohydrate substituting sucrose in the traditional creamer. FiberCreme with different fiber sources were used including isomalto oligosaccharides (FC01), inulin (FC05) and isomaltodextrin (FC14). The FiberCreme added was 12% of weight of the rice grain. The addition of FiberCreme in cooked rice increase the total fat content from 0.33% (control rice) to 3.17%-3.33% (FiberCreme rice) but decrease the total carbohydrates content to 89.18%-89.43%, the total dietary fiber increase by 5.18%, 2.76% dan 4.5% in FC01, FC05 and FC14, respectively, and the resistant starch increase from 3.40% (control rice) to 5.11% (FC01 rice), 5.21% (FC05 rice) and 4.92% (FC14 rice), respectively. In human studies, it showed that addition of FiberCreme decrease the Glycemic Index (GI) of FiberCreme added cooked rice to 73.8 (FC01 rice), 70.7 (FC05 rice) and 76.5(FC14 rice) compared to 79.8 (control rice).